Physical mechanism behind and access to the I-mode confinement regime in tokamaks. (31st July 2020) - Manz, P.; Happel, T.; Stroth, U.; Eich, T.; Silvagni, D.
Abstract: The I-mode is an attractive confinement regime for future tokamak based fusion reactors. A model is presented which explains the I-mode regime by the reduction of ITG turbulence near the separatrix at low collisionality, where the separatrix ion temperature can exceed the electron temperature. Drift-Alfvén-turbulence develops, with large and small-scale fluctuations being suppressed by phase randomization and finite-Larmor-radius effects, respectively. The intermediate scales form a broad peak in the frequency spectrum, which features the same properties as the characteristic weakly coherent mode. The model, which is studied by means of gyro-fluid simulations, reproduces a number of other experimental I-mode observations, such as decoupled energy and particle transport, intermittent turbulent bursts with precursors, an operational window widening with magnetic field strength, and the challenges met when detaching the plasma.